State Policy of Ukraine in Terms of Implementing Law Enforcement Function of the Country in the Taxation Sphere - Теремецький, Владислав Іванович; Теремецький, В. І.; Теремецкий, Владислав Иванович; Teremetskyi, Vladyslav I.; Гречанюк, Сергій Костянтинович; Гречанюк, С. К.; Гречанюк, Сергей Константинович; Hrechaniuk, Serhii K.; Hrechaniyuk, Serhiy; Наливайко, Лариса Романівна; Наливайко, Л. Р.; Наливайко, Лариса Романовна; et al. (Allied Business Academies, 2021)
The current state of the formation and implementation, as well as tendencies for the development of state policy on ensuring the implementation of the law enforcement function of the country in the taxation sphere have been clarified in this research. The research was aimed at demonstrating that any legislative amendments in the taxation sphere should focus on ensuring the integrity of the tax system and the development of voluntary compliance with the current norms by taxpayers. The authors have analyzed scientific approaches regarding the peculiarities of the formation and implementation of state policy on legal provision of the law enforcement function of the country in the taxation sphere in relation to the involvement of civil society institutions into this activity and strengthening the role of information and analytical forms and methods of its realization. The authors of the article have defined the basic principles of legal entities to implement the law enforcement function of the country in the taxation sphere based on the “good governance” concept: focusing on meeting the needs of taxpayers, which is in the public interest of civil society and the state in the whole; stability and long-term orientation of the tax policy; achieving efficiency, effectiveness, openness, transparency in the activities of state authorities; competence and ethical behavior of their officials.

У цьому дослідженні з’ясовано сучасний стан формування та реалізації, а також тенденції розвитку державної політики щодо забезпечення реалізації правоохоронної функції країни у сфері оподаткування. Метою дослідження було продемонструвати, що будь-які законодавчі зміни у сфері оподаткування мають бути спрямовані на забезпечення цілісності податкової системи та розвиток добровільного дотримання чинних норм платниками податків. Авторами проаналізовано наукові підходи щодо особливостей формування та реалізації державної політики щодо правового забезпечення правоохоронної функції країни у сфері оподаткування щодо залучення до цієї діяльності інститутів громадянського суспільства та посилення ролі інформації й аналітичних форм і методів її реалізації. Автори статті визначили основні принципи реалізації юридичними особами правоохоронної функції країни у сфері оподаткування на основі концепції «доброго управління»: орієнтація на задоволення потреб платників податків, що відповідає суспільним інтересам громадянського суспільства та держави в цілому; стабільність та довгострокова спрямованість податкової політики; досягнення ефективності, дієвості, відкритості, прозорості в діяльності органів державної влади; компетентність та етична поведінка своїх посадових осіб.
Teremetskyi V. State Policy of Ukraine in Terms of Implementing Law Enforcement Function of the Country in the Taxation Sphere / V. Teremetskyi, S. Hrechaniyuk, L. Nalyvaiko, V. Terekhov, O. Salmanova, I. Chuprikova, M. Nazarenko // Journal of Legal, Ethical and Regulatory Issues. - Vol. 24. - SI 1. - Allied Business Academies, 2021. - 9 р.
Keywords: state policy; tax policy; law enforcement function of the country; taxation; legal provision; civil society institutions; principles of activity; державна політика; податкова політика; правоохоронна функція країни; оподаткування; правове забезпечення; інститути громадянського суспільства; принципи діяльності; Research Subject Categories::LAW/JURISPRUDENCE